Assessment of curbside anticoagulation pharmacy visits on clinical outcomes and patient satisfaction. Issue 5 (8th February 2022) - Juodvalkis, Alana; West, Kacey; Eash, Toni; Foster, Todd; Bentfield, Brad
Abstract: Introduction: During the coronavirus disease 2019 (COVID‐19) pandemic, curbside international normalized ratio (INR) checks were implemented to monitor patients on warfarin therapy. Because of the lack of available data, clinical outcomes and patient satisfaction were assessed to determine if the implementation of curbside visits could be considered as an alternative to the standard of care. Objectives: The objectives were to assess clinical outcomes, safety, and patient satisfaction in a patient cohort whose anticoagulation was managed inside the clinic in 2019 compared with the same patients managed in the curbside setting in 2020. Methods: In this retrospective study, INR time in therapeutic range (TTR) was used as a marker for clinical appropriateness of anticoagulation therapy. Data were also prospectively collected in the form of patient satisfaction surveys. Adverse events and hospitalizations were assessed to ensure patient safety was not omitted. Results: The median TTR in 2019 was significantly higher than in 2020, 95.7% (interquartile range [IQR] 33.3%) vs 84.3% (IQR 45.2%) ( z = −3.99, P < .001). Clinically, the mean TTR remained higher in 2019 than in 2020 (81.3% vs 74.7%). Less patients experienced bleeding events in 2020, and there was an average of 1 less visit per patient in 2020 compared with 2019. Surveys indicated that more patients would like their visits to occur inside the clinic if there were no concerns for a pandemic. Conclusion: Anticoagulation management assessed by TTR was significantly lower in the 2020 time frame compared with 2019; however, the average TTR in both time frames was above the clinically accepted threshold of adequate anticoagulation control. Patients demonstrated favor toward in‐person visits unless there were concerns for a pandemic. If needed, curbside visits could be considered in the future at this site; however, more studies would need to be done to assess the impact of curbside visits at other institutions.